Differentiating Primary Sclerosing Cholangitis from Similar Diseases of Autoimmune Origin - Kunovsky, Lumir; Dite, Petr; Hornakova, Lubomira; Dolina, Jiri; Uvirova, Magdalena; Kojecky, Vladimir; Martinek, Arnost; Jabandziev, Petr (Journal of gastrointestinal and liver diseases, 2021)
Primary sclerosing cholangitis (PSC) is a rare cholestatic liver disease. Differential diagnostics can confuse it with immunoglobulin (Ig) G4-related sclerosing cholangitis (SC), an IgG4-related disease with clearly proven autoimmune origin. Differential diagnosis is made even more challenging because PSC with increased IgG4 levels (PSC-increased IgG4) also occurs. In order to facilitate their differential diagnosis, we reviewed recent literature regarding the etiologies, identifying characteristics, the most useful diagnostics, treatment, and the progression of these partially similar diseases. It is clear that PSC's pathogenesis differs from that of IgG4-related SC. In any differential diagnosis between PSC and PSC-increased IgG4, high IgG1 and low or normal IgG2 levels are characteristic for patients with PSC. Histological examination of the biliary tree wall in patients with IgG4-related SC typically reveals such changes as storiform fibrosis, obliterative phlebitis, and venulitis. These are absent in PSC-increased IgG4, which is characterized by a typical circular thickness in different parts of the biliary ducts. Finally, PSC is associated with inflammatory bowel disease, which is rare in IgG4-related SC, and more frequently is associated with cholangiocarcinomas and colon cancers. As distinct from IgG4-related SC, PSC is not a primary autoimmune disease.
Keywords: autoimunitní nemoci; diferenciální diagnóza; Diagnosis, Differential; Immunoglobulin G; žlučové cesty intrahepatální; Humans; imunoglobulin G; Cholangitis, Sclerosing; Bile Ducts, Intrahepatic; Autoimmune Diseases; sklerozující cholangitida; lidé